2014
DOI: 10.1007/s00726-014-1683-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct chromatographic enantioresolution of fully constrained β-amino acids: exploring the use of high-molecular weight chiral selectors

Abstract: To the best of our knowledge enantioselective chromatographic protocols on β-amino acids with polysaccharide-based chiral stationary phases (CSPs) have not yet appeared in the literature. Therefore, the primary objective of this work was the development of chromatographic methods based on the use of an amylose derivative CSP (Lux Amylose-2), enabling the direct normal-phase (NP) enantioresolution of four fully constrained β-amino acids. Also, the results obtained with the glycopeptide-type Chirobiotic T column… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…[25][26][27] Thereby, additives regulate the strength of the ionic interactions between selector and analyte molecules. They influence the solvation extent of both interaction partners (i.e., the formation of an ion-cloud around the charged sites and of a double layer of a particular thickness in dependence on the ionic strength on the charged surface, respectively) and act as displacers, which may result in a profound impact on the retention and the quality of the enantioseparation process 25,[28][29][30][31] .…”
Section: Effect Of Basic and Acidic Additivesmentioning
confidence: 99%
“…[25][26][27] Thereby, additives regulate the strength of the ionic interactions between selector and analyte molecules. They influence the solvation extent of both interaction partners (i.e., the formation of an ion-cloud around the charged sites and of a double layer of a particular thickness in dependence on the ionic strength on the charged surface, respectively) and act as displacers, which may result in a profound impact on the retention and the quality of the enantioseparation process 25,[28][29][30][31] .…”
Section: Effect Of Basic and Acidic Additivesmentioning
confidence: 99%
“…Apparent thermodynamic parameters have been calculated, and entropically-and enthalpically-driven separations discussed as part of the molecular recognition process. The enantioresolutions of free unusual AAs and constraint -AAs on teicoplanin-and polysaccharide-based columns have been compared[26,27]. The optimized methods proved applicable for enantiomeric purity (enantiomeric excess, ee) control.[27].…”
mentioning
confidence: 99%
“…If chiral cavities are opened, the inclusion interactions of the analyte are reduced and the retention time of the analyte is reduced [ 24 , 28 , 29 , 30 ]. Pirkle and Welch studied the effect of an alcohol modifier on enantioselectivity and found that the effect of a modifier depends on the structure of the analyte [ 31 , 32 , 33 ]. Based on VCD measurements Grinberg et al observed conformational changes of the chiral stationary phase in the presence of polar solvents.…”
Section: Resultsmentioning
confidence: 99%